243 The effect of reduced street-lighting on road collisions in England and Wales 2000–2013. (1st September 2016) - Steinbach, Rebecca; Perkins, Chloe; Armstrong, Ben; Edwards, Phil
Abstract : Background: Many local authorities in England and Wales have reduced street lighting at night to save money and reduce carbon emissions. Reductions in street-lighting, however, have attracted considerable public concern about road safety. While there is evidence that increasing street-lighting can reduce collisions it is unknown wheather reducing street-lighting can increase collisions. We quantified the effect of four street lighting adaptation strategies (switch off, part-night lighting, dimming and white light) on road traffic collisions in England and Wales. Methods: Observational study based on analysis of geographically coded police data on road traffic collisions in 62 local authorities. Conditional Poisson models were used to analyse longitudinal changes in the counts of night-time collisions relative to day-time collisions occurring on affected roads during 2000– 2013. Effect estimates were adjusted for regional temporal trends in collisions. Results: There was no evidence that switch-off (rate ratio 0.97; 95% confidence interval 0.82 to 1.15); part-night lighting (RR 0.95; 95% CI: 0.84 to 1.07); dimming (RR 1.00; 95% CI: 0.91 to 1.10); or changes to white light (RR 1.01; 95% CI: 0.93 to 1.09) were associated with a change in collisions at night relative to collisions during the day. Conclusions: This study found little evidence of harmful effects of switch off, part-night lighting, dimming, or changes to white light/LEDs on road collisions in England and Wales.